Preservation of relational databases : significant properties in the preservation of relational databases - Freitas, Ricardo André Pereira (2011)
Relational Databases are the most frequent type of databases used by organizations worldwide and are the base of several information systems. As in all digital objects, and concerning the digital preservation of them, the significant properties (significant characteristics) must be defined so that adopted strategies can be evaluated. First, a neutral format (hardware and software independent) – DBML – was adopted to persue the goal of dematerialization and to achieve a standard format in the digital preservation of the relational databases data and structure. Currently, in this project, we walk further in the definition of the significant properties by considering the database semantics as an important characteristic that should also be preserved. For the representation of this higher level of abstraction we are going to use an ontology based approach. We extract the entity-relationship model from the database in order to represent it as an ontology.